1996
DOI: 10.1093/fampra/13.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Prevention in practice: results of a 2-year follow-up of routine health promotion interventions in general practice

Abstract: This study confirms the low impact of health checks on the self reported modification of cardiovascular risk factors and shows that maintenance of appropriate health behaviour change is no more likely in those who have received a health check.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…The "prevention in practice" study by Dowell et al 19 in Leeds, England, used a quasiexperimental design to compare self reported vigorous exercise in the two weeks before and two years after a health check aimed at changing multiple risk factors for the prevention of stroke and heart disease. A 12% stratified sample of patients was chosen from 18 general practices in the Yorkshire and Southwest Thames regions, and these patients were invited for a health check, yielding 1687 patients in the intervention group and 3937 patients in the control group without a health check.…”
Section: Resultsmentioning
confidence: 99%
“…The "prevention in practice" study by Dowell et al 19 in Leeds, England, used a quasiexperimental design to compare self reported vigorous exercise in the two weeks before and two years after a health check aimed at changing multiple risk factors for the prevention of stroke and heart disease. A 12% stratified sample of patients was chosen from 18 general practices in the Yorkshire and Southwest Thames regions, and these patients were invited for a health check, yielding 1687 patients in the intervention group and 3937 patients in the control group without a health check.…”
Section: Resultsmentioning
confidence: 99%
“…Health check-ups have been demonstrated to improve the frequency of preventive care and support regular discussions on changing health behaviour in middle age [57, 58] and have also been found to improve the quality of preventative care [59]. Further, adults who received ongoing care from regular visits to the GP are found to be more likely to receive the preventive services as recommended by policy guidelines [18].…”
Section: Discussionmentioning
confidence: 99%
“…1,3,11 Furthermore, patients often struggle with adopting lifestyle changes; mere knowledge is not sufficient to result in change in behavior. 12 The gold standard approach to lifestyle intervention was utilized in the NIH-sponsored Diabetes Prevention Program. 8 However, such an intervention requires assembly of new teams of health care providers.…”
Section: Initial Patient Assessmentmentioning
confidence: 99%